Close: Closure of patent foramen ovale, oral anticoagulants or antiplatelet therapy to prevent stroke recurrence: Study design. Issue 6 (August 2016) - Mas, Jean-Louis; Derumeaux, Geneviève; Amarenco, Pierre; Arquizan, Caroline; Aubry, Pierre; Barthelet, Martine; Bertrand, Bernard; Brochet, Eric; Cabanes, Laure; Donal, Erwan; Dubois-Randé, Jean-Luc; Durand-Zaleski, Isabelle; et al.
Rationale: Currently available data do not provide definitive evidence on the comparative benefits of closure of patent foramen ovale, oral anticoagulants and antiplatelet therapy in patients with patent foramen ovale-associated cryptogenic stroke Aim: To assess whether transcatheter patent foramen ovale closure plus antiplatelet therapy is superior to antiplatelet therapy alone and whether oral anticoagulant therapy is superior to antiplatelet therapy, for secondary stroke prevention in patients aged 16 to 60 years with a large patent foramen ovale or a patent foramen ovale associated with an atrial septal aneurysm, and an otherwise unexplained ischaemic stroke or retinal ischaemia. Sample size: Six hundred and sixty-four patients were included in the study. Methods and design: CLOSE is an academic-driven, multicentre, randomized, open-label, three-group, superiority trial with blinded adjudication of outcome events. The trial has been registered with Clinical Trials Register (Clinicaltrials.gov, NCT00562289). Patient recruitment started in December 2007. Patient follow-up will continue until December 2016. Expected mean follow-up = 5.6 years. Study outcomes: The primary efficacy outcome is the occurrence of fatal or nonfatal stroke. Safety outcomes include fatal, life-threatening or major procedure- or device-related complications and fatal, life-threatening or major haemorrhagic complications. Discussion: CLOSE is the first specifically designed trial to assess the superiority of patent foramen ovale closure over antiplatelet therapy alone and the superiority of oral anticoagulants over antiplatelet therapy to prevent stroke recurrence in patients with patent foramen ovale-associated cryptogenic stroke.